Direct detection of Pu-242 with a metallic magnetic calorimeter gamma-ray detector - Bates, C.; Pies, Christian; Kempf, Sebastian; Hengstler, Daniel; Fleischmann, Andreas; Gastaldo, Loredana; Enss, Christian; Friedrich, S. (Journal of low temperature physics, 2016)
Cryogenic high-resolution $$γ $$γ-ray detectors can improve the accuracy of non-destructive assay (NDA) of nuclear materials in cases where conventional high-purity germanium detectors are limited by line overlap or by the Compton background. We have improved the performance of gamma detectors based on metallic magnetic calorimeters (MMCs) by separating the 0.5 $$× $$×2 $$× $$×0.25 mm$$^{3}$$3Au absorber from the Au:Er sensor with sixteen 30-$$\upmu $$μm-diameter Au posts. This ensures that the entire $$γ $$γ-ray energy thermalizes in the absorber before heating the Au:Er sensor, and improves the energy resolution at 35 mK to as low as 90 eV FWHM at 60 keV. This energy resolution enables the direct detection of $$γ $$γ-rays from Pu-242, an isotope that cannot be measured by traditional NDA and whose concentration is therefore inferred through correlations with other Pu isotopes. The Pu-242 concentration of 11.11 $$± $$±0.42 % measured by NDA with MMCs agrees with mass spectrometry results and exceeds the accuracy of correlation measurements.
Published: 27 October 2015
Gesehen am 23.04.2020